Selection of Candidate Reference Genes for Gene Expression Analysis in Kentucky Bluegrass (Poa pratensis L.) under Abiotic Stress - Niu, Kuiju; Shi, Yi; Ma, Huiling (Frontiers in Plant Science, 2017)
Kentucky bluegrass (Poa pratensis L.) belong to Gramineae and is widely used in lawns, golf courses, landscapes and sport fields as a prominent cool-season grass. Gene expression patterns during different stages of plant development can provide clues towards the understanding of its biological functions. The selection and validation of reference genes are the first steps in any real-time quantitative PCR gene expression study. Therefore, suitable reference genes are necessary for obtaining reliable results in real-time quantitative PCR analyses of Kentucky bluegrass. In the present study, 9 candidate reference genes were chosen, and their expression stability in the leaves and roots of Kentucky bluegrass under different stresses (drought, salt, heat, and cold) were evaluated using the GeNorm, NormFinder, BestKeeper, and RefFinder programs. The results showed that the expression stability of the candidate reference genes was dependent on the experimental conditions. The combination of SAM with GAPDH was the most stable in leaves under salt stress and cold stress, while TUB combined with ACT or GAPDH was stable in roots under salt or cold stress, respectively. ACT and SAM maintained stable expression in drought-treated leaves, and GAPDH combined with ACT was stable in drought-treated roots. SAM and TUB exhibited stable expression in heat-treated leaves. ACT and RPL were stable in heat-treated roots. In addition, the expression patterns of PpFEH in response to drought and cold stress were used to confirm the reliability of the selected reference genes, indicating that the use of an inappropriate reference gene as the internal control will cause erroneous results. This work is the first study on the expression stability of reference genes in Kentucky bluegrass and will be particularly useful in the selection of stress-tolerance genes and the identification of the molecular mechanisms conferring stress tolerance in this species.